Peran Komunikasi Pesantren dalam Pemberdayaan Petani CSR Agribisnis di Al-Ittifaq Ciwidey - Muhammad Rizal Zulfikar; Feliza Zubair; Agus Rahmat (REFORMASI, 2025)
This study analyzes the role of communication of Al-Ittifaq Islamic Boarding School in empowering farmer communities as an implementation of Corporate Social Responsibility (CSR) through an agribusiness program in Ciwidey, Bandung Regency. Using a qualitative approach with a case study method referring to Cresswell, this study explores the communication strategies used by Islamic boarding schools in building community welfare. Data were collected through in-depth interviews, participatory observations, and document analysis. The results of the study indicate that Al-Ittifaq Islamic Boarding School uses a dialogic and participatory communication model in empowering farmers, which includes the transfer of agricultural technology, the formation of farmer groups, and the development of marketing networks. The Islamic boarding school's CSR program has succeeded in increasing the productivity and welfare of local farmers through the integration of religious values with modern agribusiness practices. Effective communication is the key to the success of the empowerment program, which has an impact on increasing farmer income by up to 40% and sustainable economic development in the Ciwidey area.e.Penelitian ini menganalisis peran komunikasi Pondok Pesantren Al-Ittifaq dalam pemberdayaan komunitas petani sebagai implementasi Corporate Social Responsibility (CSR) melalui program agribisnis di Ciwidey, Kabupaten Bandung. Menggunakan pendekatan kualitatif dengan metode studi kasus yang merujuk pada Cresswell, penelitian ini mengeksplorasi strategi komunikasi yang digunakan pesantren dalam membangun kesejahteraan masyarakat. Data dikumpulkan melalui wawancara mendalam, observasi partisipatif, dan analisis dokumen. Hasil penelitian menunjukkan bahwa Pesantren Al-Ittifaq menggunakan model komunikasi dialogis dan partisipatif dalam pemberdayaan petani, yang mencakup transfer teknologi pertanian, pembentukan kelompok tani, dan pengembangan jaringan pemasaran. Program CSR pesantren berhasil meningkatkan produktivitas dan kesejahteraan petani lokal melalui integrasi nilai-nilai agama dengan praktik agribisnis modern. Komunikasi yang efektif menjadi kunci keberhasilan program pemberdayaan, yang berdampak pada peningkatan pendapatan petani hingga 40% dan pengembangan ekonomi berkelanjutan di wilayah Ciwidey.